Apakah Partisipasi Masyarakat Dapat Mencegah Korupsi ? - Shadu Satwika Wijaya (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2022)
The Indonesian government has developed policies aimed at encouraging village governments to learn to do business. Through the allocation of funds given to the village government, it is hoped that the village can develop a village-owned business. In its development, village governments in Indonesia have responded well to this policy, so that currently many villages have business units. However, as a public business, it is necessary to ask whether the village business has been carried out in an accountable manner. Therefore, this study aims to analyze the accountability system of village business management in Indonesia. This study uses a public governance approach, because village businesses use public funds, so public involvement is very important in its management. This research was conducted using quantitative methods, targeting BUMDes in Banyumas. The results of the study show how public participation can prevent corruption.